Metamaterial – based sensor for detection of biomolecules - Mat Rusni, Izyani (2017)
Recently, the interest of microwave signals for biological detection applications using metamaterial structure as a biosensor element is tremendously increased due to high Q factor value and stronger electric field compared to the conventional microwave sensor. This research refers to a proof-of-concept study concerning the development of a metamaterial based sensor for biomolecule detection.